The Effect Of Otago Home Exercises On Reducing The Risk Of Falling On The Elderly At The Batara Hati Mulia Foundation, Gowa Regency - Virny Dwiya Lestari; Rahmat Nugraha Akib; Aco Tang; Nugraheni Widyastuti; Andi Rahmaniar; Yeri Mustari (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The Otago Home Programme Exercise is an exercise program that combines strengthening exercises, balance exercises, and walking programs. This exercise program is specifically designed to reduce the risk of falls, by increasing the strength of the lower movement muscles, improving balance, and providing walking exercises. Methods: This study aims to determine the effect of Otago home exercises on reducing the risk of falling the elderly at the Batara Hati Mulia Foundation. This research is a pre-experimental study with pre-test and post-test one group design with a total sample of 30 people. The place of research was conducted at the Batara Hati Mulia Foundation Gowa Regency. A tool to measure the risk of falls is the Berg Balance Scale (BBS). Result: The results of the study are that there is a decrease in the risk of falling in the elderly at the Batara Hati Gowa Foundation based on measurements of the BBS, namely a pre-test value of 37,36 to a post-test of 48.73 because after being given Otago Home Exercises can improve static balance and dynamic balance and increase the stability of postural muscles so that it can reduce the risk of falls in the elderly. Conclusion: Otago Home Exercises can reduce the risk of falls in the elderly at the Batara Hati Gowa Foundation.